Faktor-Faktor yang Mempengaruhi Rendahnya Tingkat Kunjungan di Perpustakaan Dinas Perpustakaan dan Kearsipan Kota Padang - Hayuni, Rahimah; Nurizzati, Nurizzati (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2017)
The writing of this paper discusses the factors that affect the low level of visitors at Perpustakaan Dinas Perpustakaan Kota Padang.The method used in writing this paper is descriptive method. Source of data obtained from the librarian at Dinas Perpustakaan dan Kearsipan Kota PadangÂ and some general public. The data collection techniques were conducted by interviewing some of the general public .Based on the analysis of data that has been obtained, it can be concluded that (1) the factors that affect the low level of visitors in Library of Dinas Perpustakaan dan Kearsipan Kota Padang, First, the location is not strategic and not widely known by the public. Second, the book collection is incomplete and visitors difficult to find the books. Next, the facilities in the library are inadequate; (2) the effort are made to increase the visitors in Library of Dinas Perpustakaan dan Kearsipan Kota PadangÂ are, the librarians have to do promotion activity, add the collection according to the needs of visitors, refinement the room by rearranging books around the reading table into the shelves that have been provided.Keyword: library, the factors , the level of visitor,Â librarian